2013
DOI: 10.1038/icb.2013.28
|View full text |Cite
|
Sign up to set email alerts
|

Full functional activity of SSL7 requires binding of both complement C5 and IgA

Abstract: Staphylococcus aureus is an opportunistic bacterial pathogen responsible for a range of diseases, from local skin infections through to life-threatening illnesses such as toxic shock syndrome. S. aureus produces an assortment of molecules designed to evade or subvert the host immune system. One example is the 23 kDa staphylococcal superantigen-like protein 7 (SSL7) that simultaneously binds immunoglobulin A (IgA) and complement C5 to inhibit complement-mediated hemolytic and bactericidal activity. The avirulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…A significantly increased survival rate (63%, p Ͻ 0.001) was also observed with equimolar amounts of the control protein SSL7. SSL7 is an S. aureus immune evasion factor previously shown to increase the survival of L. lactis in human blood (34). The addition of 0.01 and 0.1 M rS5nA also increased bacterial survival in a concentration-dependent manner (8.9 and 18.1%, respectively), but this was not statistically significant (p Ͼ 0.1).…”
Section: Recombinant S5na Increases the Survival Of L Lactis In Humamentioning
confidence: 88%
See 1 more Smart Citation
“…A significantly increased survival rate (63%, p Ͻ 0.001) was also observed with equimolar amounts of the control protein SSL7. SSL7 is an S. aureus immune evasion factor previously shown to increase the survival of L. lactis in human blood (34). The addition of 0.01 and 0.1 M rS5nA also increased bacterial survival in a concentration-dependent manner (8.9 and 18.1%, respectively), but this was not statistically significant (p Ͼ 0.1).…”
Section: Recombinant S5na Increases the Survival Of L Lactis In Humamentioning
confidence: 88%
“…L. lactis is a non-pathogenic, food grade bacterium that is rapidly killed when incubated with whole blood. Increased survival of the bacteria in blood has been used to analyze potential virulence factors (30,34). The addition of rS5nA to L. lactis in human whole blood significantly increased bacterial survival in a dose-dependent manner (Fig.…”
Section: Recombinant S5na Increases the Survival Of L Lactis In Humamentioning
confidence: 99%
“…Additionally, the binding of SSL7 to already activated C5b results in an inhibition of membrane attack complex (MAC) formation. Consequently, inhibition of C5a-mediated chemotaxis of inflammatory myeloid cells and C5a-dependent microbial killing relies on the presence of IgA, whereas MACmediated killing is solely dependent on SSL7 [374,382]. MAC, though, is not to be effective against Gram-positive bacteria due to their thickened outer wall.…”
Section: The Immunoglobulin/complement-inhibiting Sslsmentioning
confidence: 95%
“…Recent evidence, however, shows that MAC does form on Gram-positive bacteria and SSL7 can inhibit this [374,388]. In vivo studies have shown that SSL7 can inhibit the migration of neutrophils into the peritoneum in response to S. aureus and that this activity is significantly more effective in the presence of IgA binding [374]. SSL7 has the ability to block the binding of IgA to its Fc receptor so it could potentially prevent FcαRI effector functions that include phagocytosis of microbes [389].…”
Section: The Immunoglobulin/complement-inhibiting Sslsmentioning
confidence: 96%
See 1 more Smart Citation